Peranan Badan Narkotika Nasional dalam Menanggulangi Tindak Pidana Liquid Vape yang Mengandung Narkotika - Yoga Wira Pranata; I Nyoman Putu Budiartha; Ni Made Sukaryati Karma (Jurnal Preferensi Hukum, 2022)
The circulation of electronic cigarettes or vapes has now developed quite rapidly, liquid vapes are liquids that are the main ingredients of vapes with different flavors, aromas and nicotine levels. There are many ways to make liquid that narcotics dealers can do by mixing synthetic marijuana and liquid liquid which actually includes a new type of synthetic narcotic. The purpose of this study is to examine methods of preventing and overcoming the circulation of vape liquid containing Narcotics by the National Narcotics Agency and to examine the obstacles of the National Narcotics Agency in preventing and overcoming the sale and purchase of liquid containing Narcotics. This study uses empirical legal research with a conceptual and sociological approach. The legal materials used are primary and secondary data. To obtain valid data, the researchers used the method of observation and interview, then the data were analyzed qualitatively descriptively. The results showed that the prevention method by providing counseling, checking every three months at vape shops and community groups who use vaping in Denpasar City, regarding this obstacle lies in the difficulty of finding suspects because the cell system is disconnected in the Narcotics network between sellers, Narcotics dealers who do not know each other. Regarding the conclusions above, the researcher suggests that the Denpasar City National Narcotics Agency should do prevention through early education regarding the dangers of this type of liquid Narcotics so that it does not spread among students or adolescents.